Navigating SWOT-FANP with GSM method to prioritize the strategic location - Lee, Yun-Huei (Technological and Economic Development of Economy, 2015)
This paper proposes a SWOT-FANP (strengths, weaknesses, opportunities, and threats – fuzzy analytic network process) analysis, together with the grand strategy matrix method (GSM) to deal with the multiple-criteria decision-making problem of location selection for a second tier city in China. This hybrid method can not only combine both qualitative and quantitative information and utilize fuzzy logic to eliminate vagueness, subjectivity, and imprecision, it can also clearly represents the competitive position of second-tier cities on a the quadrant coordinate to help an enterprise choose a strategy for development. To this end, I empirically chose a multinational pharmaceutical enterprise (MNE) as an illustrative example. The results reveal that Suzhou and Chongqing cities are in the best positions in the competition as a result of having external opportunities for development and internal competing strength. Moreover, the MNE could adopt a niche-focus strategy for the market by focusing on specific ailments to which people in Chinese communities are vulnerable to strengthen their competitive strengths. This study demonstrates and validates that such an enhanced methodology is viable and highly capable of providing enriched insights regarding strategic decision-making management in complex real-world situations.